Dynamic Structure of Nuclear States - Rowe, David J.; Trainor, Lynn E.H; Wong, Samuel S.M (University of Toronto Press, 2020)
The Mont Tremblant International Summer Scholl was primarily concerned with the dynamic structure of nuclear states. The papers presented at that summer school in August, 1971, are reproduced in this volume. Five deal with theories of the structure and systematics of nuclear states; six with clustering and fission phenomena; and three with the study of nuclear structure using electromagnetic excitation. The remaining papers deal with nucleosynthesis and the formation of super-heavy elements, selected topics in intermediate energy physics, and experiments at meson factories. Nine brief statements of recent results by participants in the school and a summary of the conference highlights complete the volume
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2020)
Keywords: SCIENCE / Physics / Nuclear